Order Visibility and Performance of Level 4 Private Hospitals in Kenya - Karoki, Anne Wanjiru; Wachiuri, Elizabeth; Nyaberi, Duncan (International Journal of Supply Chain and Logistics, 2026)
Purpose: The main focus of this study was to establish the role of order visibility on performance of level 4 private hospitals in Kenya. Methodology: The study was anchored on General Systems Theory. The study adopted cross-sectional research design and positivist research paradigm. The unit of analysis was the 368 level 4 private hospitals in Kenya while the unit of observation was heads of procurement, quality assurance, finance, risk and compliance and audit. Therefore, the target population was 1840 heads of departments in level 4 private hospitals in Kenya. Krejcie and Morgan (1970) formula was adopted in calculating appropriate sample size. From the formula, the sample size for the study was 320 respondents. The sample was selected using stratified random sampling. The study used primary data collected using semi-structured questionnaires. The study collected both qualitative and quantitative data, Qualitative data was analysed using content analysis a presented in prose form. Quantitative data was analysed using SPSS version 28. Descriptive statistics including means, percentages, frequencies and standard deviations were used to analyse quantitative data. Inferential statistics using Pearson R correlation, simple regression and multiple regressions were also computed. Findings: The study found that order visibility is statistically significant in explaining performance of private hospitals in Kenya. The influence was found to be positive. This means that unit improvement in order visibility would lead to an increase in performance of private hospitals in Kenya. Unique Contribution to Theory, Practice and Policy: Based on the findings, the study concluded that order visibility positively and significantly influences with performance of private hospitals in Kenya. The study recommends management of Private Hospitals to Implementing a comprehensive EHR system that will help hospitals digitize patient records, treatment plans, and medication orders. It enables real-time access to patient information, test results, and treatment histories, making it easier for healthcare professionals to coordinate patient care effectively. This leads to improved order visibility within the hospital.